Identifying women's needs to adjust to postpartum changes: a qualitative study in Iran - Mahboobeh Asadi; Mahnaz Noroozi; Mousa Alavi (BMC, 2022)
Abstract Background The transition to motherhood is associated with stress because of extensive and rapid changes to which women need to be able to adjust. To help women adjust to postpartum changes, their needs during this period must be identified. Therefore, the present qualitative study explored the needs of women for adjusting to postpartum changes. Methods In this study, 29 participants were selected through purposive sampling with maximum variation in Isfahan, Iran. Data was collected through in-depth individual interviews, daily notes, and field notes, and analyzed using conventional qualitative content analysis. Results Data analysis led to the emergence of 5 main categories: "the need to receive social support," "the need to receive a sense of worth from the husband," "the need to compensate and improve the situation," "the need to create socio-cultural changes," and "the need for training." Conclusions According to the results of the study, in order to adjust to the changes in the postpartum period, and in addition to their efforts to compensate and improve the situation, women need to be supported by their husbands, family members and acquaintances, healthcare team, and society in various dimensions. Moreover, they should receive the information they need to turn the challenges of this period into an opportunity for growth.